" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
f(-3) = -3a+b=-15→ pers 1
f(3) = 3a+b=9 →pers 2
eliminasi pers 1 dan 2
-3a + b = -15
3a + b = 9
----------- -
-6a = -24
a = 4
-3a + b = -15
-3.4 + b = -15
b = -15 + 12
= -3
f(-2) = (-2).4 + -3 = -11
f(2) = 2.4 + -3 = 5
jadi f(-2) + f(2) = -11 + 5 = 6
• -3a+b = -15
• 3a+b =9
dieliminasi mendapat nilai a=4 dan b=-3
f(-2)+f(2)= (4*(-2)+(-3)) + (4*(2)+(-3))
-8-3+8-3
-11+5
=-6